Secure remote access to an Internet Web server. - Gilmore, C. (IEEE Network : the magazine of global information exchange)
We address the problem of secure remote access to a site's internal Web server from outside the firewall. The goal is to give authorized users access to sensitive information, while protecting the information from others. We implemented our solution using a one-time password scheme for client authentication and secure socket layer (SSL) for confidentiality. Our main design considerations were security, performance, ease of use, availability, and scale. We were further constrained by the desire to leave our firewall and local infrastructure unchanged